Chemical profiling of secondary metabolites of Eugenia uniflora and their antioxidant, anti-inflammatory, pain killing and anti-diabetic activities: a comprehensive approach - Sobeh, Mansour; El-Raey, Mohamed; Rezq, Samar; Abdelfattah, Mohamed A. O.; Petruk, Ganna; Osman, Samir; El-Shazly, Assem M.; El-Beshbishy, Hesham A.; Mahmoud, Mona F.; Wink, Michael (Journal of ethnopharmacology, 2019)
Ethnopharmacological relevance: The red Brazilian cherry, Eugenia uniflora, is widely used in traditional medicine. The aim of this study was to investigate the phytochemical composition of a methanol extract from leaves of E. uniflora and characterization of the isolated compounds. In addition, we aimed to determine the antioxidant activities in vitro and in a cell-based (HaCaT cell) model. We also studied the anti-inflammatory, analgesic, antipyretic and antidiabetic activities in relevant rat models. The molecular mode of action of the antidiabetic activities was also investigated. Materials and methods: UV, MS, and NMR (1H, 13C, DEPT, COSY, HMQC, and HMBC) were used to identify the secondary metabolites. Antioxidant effects were determined in vitro and in HaCaT cells. The ani-inflammatory and antidibetic activities were studied in experimental animals. Results: In this work, a new compound, gallic acid 3-O-[6′-O-acetyl-β-D-glucoside], along with 16 known plant secondary metabolites (PSM) were isolated, characterized using UV, MS, and NMR (1H, 13C, DEPT, COSY, HMQC, and HMBC). Noticeable antioxidant effects were determined in HaCaT cells: The extract reduced the elevated levels of ROS and p38 phosphorylation and increased the reduced glutathione (GSH) content induced by UVA. The extract showed substantial anti-inflammatory activities in vivo: It diminished the edema thickness in carrageenan-induced hind-paw edema rat model and lowered the leukocyte migration into the peritoneal cavity. In rats, central and peripheral anti-nociceptive properties were also observed: The extract reduced the number of writhing in acid induced writhing and increased the latency time in hot plate test. Furthermore, adequate antipyretic effects were observed: The extract reduced the elevated rectal temperature in rats after intraperitoneal injection of Brewer's yeast. Moreover, the extract possessed robust anti-diabetic activity in streptozotocin (STZ) -diabetic rats: It markedly reduced the elevated serum glucose and lipid peroxidation levels and increased the insulin concentration in serum with higher potency than the positive control, glibenclamide. These effects might be associated with the interaction of PSM with the conserved amino acid residues of human pancreatic α-amylase (HPA), maltase glucoamylase (MGAM-C) and aldose reductase (ALR2) revealing considerable binding affinities. Conclusion: A plethora of substantial pharmacological properties indicates that Eugenia uniflora is a good antioxidant and a sustainable by-product with solid therapeutic potential for treating diabetes, inflammation, pain and related oxidative stress diseases.
Gesehen am 19.07.2019